VIDEO MEDIA-BASED LEARNING MODEL ON ECOSYSTEM SCIENCE MATERIAL FOR GRADE V STUDENTS IN SDN BEUTONG - Nurmiati; Siti Mayang Sari; Akmaluddin; Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The text discusses the challenges faced by educators in improving learning success, particularly in the field of science at SDN Beutong. Science education is crucial as it relates to everyday life and understanding the universe. To optimize the learning process, it is important for teachers to use effective teaching methods that allow students to efficiently learn and achieve desired results. One way to improve science learning is by incorporating video media, specifically in teaching about ecosystems. Video media helps to engage students, encourage critical thinking, and increase the effectiveness of learning. The article aims to describe the video media-based learning model used in teaching science ecosystem material to fifth-grade students at SDN Beutong. The study utilized a descriptive qualitative method, with researchers observing the learning process through direct observation without active participation. The research findings indicated that the use of an animated video-based simulation model improved student learning outcomes in ecosystem learning at SDN Beutong.